God's double agent : the true story of a Chinese Christian's fight for freedom - Fu, Xiqiu; French, Nancy, 1974- (Grand Rapids, Michigan : Baker Books, a division of Baker Publishing Group, 2013)
Tens of millions of Christians live in China today, many of them leading double lives or in hiding from a government that relentlessly persecutes them. Bob Fu, whom the Wall Street Journal called "The pastor of China's underground railroad," is fighting to protect his fellow believers from persecution, imprisonment, and even death. God's Double Agent is his fascinating and riveting story.
Includes bibliographical references.
Keywords: Fu, Xiqiu; Christian biography -- China; Christian biography -- United States; Christianity -- China; Persecution -- China -- History -- 20th century; Christians -- China -- History -- 20th century; Autobiography; History; Christian biography; Autobiography